Response Analysis Of Urban Vaname (Litopenaeus Vannamei) Which Is Exposed to Crude Protein Zoothamniumpenaei Oral and Maintained In Ponds - M. Ferri Tahta Rohmin (Universitas Airlangga, 2017)
ABSTRACTThe objectives of this study were immune response, specific growth rate and survival rate of shrimp vaname (Litopenaeus vannamei) in ponds. The research method used was experimental to know the effect of feed use and added crude protein Zoothamnium penaei on vaname shrimp (Lithopenaeus vannamei) in pond. The sample used is shrimp vaname (Lithopenaeus vannamei) as much as 10,000 heads of juvenile stadia. The food used is commercial feed added crude protein Zoothamnium penaei with a dose of 150 μl / head, which is given 7 times every 7 days interval from the age of 1 day up to Shrimp aged 56 days in ponds. The results showed that there was an increase of immune response (increase of THC and DHC) due to feeding added by Zoothamnium penaei crude. The highest total of Haemocytes (THC) occurred in commercial-fed shrimp and added crude protein ie 56,58 x 106 cell / ml, And the lowest in shrimp shrimp that is not given its crude protein 23.57 x 106 cells / ml. Similarly, the highest Differential Haemosite Count (DHC) also occurred in shrimps fed commercial and added crude protein, 26.57% aged 60 days in ponds and 14.99% low on shrimp not given 90 day crude protein in ponds . Results of parasite shrimp infestation examination exposed with crude protein showed that the highest Zoothamnium penaei infestation was obtained in shrimp fed with artificial feed and not added crude protein Zoothamnium penaei that is 63,35% in shrimp age 90 days. While the shrimp were given artificial feed and added crude protein Zoothamnium penaei infestation Zoothamnium penaei highest of 14.27% in 90 days old shrimp.The highest specific rate of vaname shrimp growth also occurred in shrimp fed commercial and added crude protein Zoothamnium penaei highest of 53.46% and the lowest 16.15% in shrimps aged 90 days in ponds. The highest shrimp life occurrence occurred in commercial vaname shrimp and added crude protein Zoothamnium penaei age of 90 days which has a higher tendency than shrimp that is not given crude protein that is 72% and 21%. The addition of Zoothamnium crude protein to commercial feed as immunostimulant material may enhance immune response, specific growth and shelf life of 30, 60 and 90 days old shrimp in ponds, so that it can be developed as an immunostimulant material.Keyword: Litopenaeus Vannamei, Zoothamnium penaei, udang vanamei